Ok so i've got the following, how can i solve this? $\displaystyle y = 2x + 2$ $\displaystyle y = \frac{^-1}{3}x + \frac{14}{3}$ Thank you
Follow Math Help Forum on Facebook and Google+
If you know how to solve systems of equations, just apply the same methods. If you don't, then first learn how. Then try the "substitution" method, since each of the two equations is already solved for "y=".
so ive got $\displaystyle 2x + 2 = \frac {^-1}{3}x + \frac {14}{3}$
Originally Posted by ADY so ive got $\displaystyle 2x + 2 = \frac {^-1}{3}x + \frac {14}{3}$ That's correct, since that equation has only x terms you can solve this Also does $\displaystyle \frac {^-1}{3}x = -\frac{1}{3}x = -\frac{x}{3}$. If it does then convention is to write it in either of the two latter forms
View Tag Cloud